STRUCTURAL-SEMANTIC AND FUNCTIONAL FEATURES OF THE WORDS «EMES», «EMEY», AND «EMEN» IN KAZAKH TURKISH (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2025)
The first known form of the complementary verb we see in Turkish texts today is «er-». It can be said that «er-/ir-« is a typical form for Köktürk, Uighur, and Karakhanid Turkish. The verbal noun «er-» in Old Turkish is used in the forms of «er-» > «e-» or «ir-» > «i-» with the omission of the «r» sound in today's Turkish dialects. In today's Kazakh Turkish, the verb «er-» > «e-» is used. The negative version of the complementary verb «e-/i-» is met with words such as «not», «tügil», «tügül», «emes», etc. in different Turkish dialects. In Kazakh Turkish, the word «emes» is generally used, and the word «tugil» is rarely used to express negativity. However, it is also seen that different forms derived from the verb root «e-», such as the word «emes», are used. In the paper, in addition to the word «emes», which is one of the inflected forms of the verbal noun «e-» and used for the negative meaning in Kazakh Turkish, the words «eme» and «emen» are used with minor differences in meaning and function. Although the functions of these words in the texts they are used sometimes have the same meanings, they can sometimes undergo minor changes.The way these three words are used in Kazakh Turkish, the places they are used, the meaning they add to the sentence or the language unions they are in, and whether they come from the same source constitute the main subject and research purpose of the paper. In this article, the functions of «emey» (not, of course), «emen» (not(im), never) and «emes» (not, -madık) in Kazakh Turkish are analyzed. It was also tried to be answered whether they are homophones and share the same root.